Team-based stepped care in integrated delivery settings. Issue 1 (1st March 2015) - Snipes, Cassandra; Maragakis, Alexandros; O'Donohue, William
Abstract : Fragmented health care delivery is recognized as increasingly problematic. Integrated care has been advanced as a reform that will improve quality of care and lower costs. Despite the application of integrated care systems in the United States, there has been a limited amount of empirical work explicating the most effective health care pathways. Stepped care has been proposed as a framework by which to implement coordinated team-based care and has gained preliminary empirical support. In this manuscript a rationale for team-based stepped care is presented, tools for implementation are provided, and future research directions are suggested.